Various Types of Lightning Observed in Mountainous Region Recorded from Kathmandu, Nepal - Adhikari, Pitri Bhakta (Journal of Institute of Science and Technology, 2023)
Vertical electric fields of lightning, generated by thunderstorms manifest on the rugged terrain in the mountainous vicinity of Kathmandu, Nepal. Diverse forms of lightning occurrences have been meticulously documented from a hill station in Kathmandu spanning a three-year interval, commencing from 2015 through 2017. Throughout this duration, cloud-to-cloud lightning discharges constituted 62.8% of the occurrences, while cloud-to-ground lightning discharges accounted for 20.4%. Additionally, 9.5% of the observed events were characterized as unusual lightning phenomena, and 2.9% were attributed to breakdown events. The elevated hills and tall structures inherent to the mountainous landscape significantly influence lightning activity, contributing to a heightened frequency of ground flashes in contrast to other areas.